Determinants of interest rate spread for new household loans in Slovenia - Požlep, Mark (knjige, 2023)
This discussion paper outlines some preliminary results regarding the determinants of interest rate spread on new housing and consumer loans in Slovenia. Using a representative sample of housing and consumer loans approved by Slovene banks be-tween October 2018 and March 2022 we examine the impact of loan specific and time varying bank factors on the interest rate spread of new loans. We find that loan specific variables (loan amount, maturity, interest rate type, presence of loan security, DSTI ratio etc.) play an important role in determining the spread. They are statistically and generally also economically significant. This suggests Slovene banks take account of loan characteristics when pricing new loans. We also find that certain bank specific time-varying characteristics (market share, total capital ratio, NPE ratio) are statistically significant and have a non-negligible impact on spreads. We observe that loans deviating from macroprudential measures introduced by the Bank of Slovenia (DSTI, maturity and LTV cap) generally have higher spreads. Nevertheless, this impact is economically small and likely imperceptible to the borrower who are credit-worthy.